Pengaruh lingkungan kerja dan pengawasan terhadap kepuasan kerja karyawan bagian produksi PT. Perindustrian dan Perdagangan Bangkinang - Munawaroh, Novia Badiatul; Indarti, Sri; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to know how Work environment variable and Supervisionby simultan and parsial of satisfaction work to PT. Perindustrian danPerdagangan Bangkinang . In this research use random sampling technique, where all of populations to be a sample used. For the knows summary samples, used slovin equation and there are 108 people’s as a sample from the total people’s of populations. This research used primary datas, where are data knows by interview and quistioner. The used analyze in this research is descriptive analyze, and then also used quantitative analyze with the make by SPSS program version 16. From result of examination which have been simultan regresi test ( uji F ) indicate that environment variable and Supervision by simultan have an effect on signifikan to work satisfaction. Result of test parsial ( Test t ) indicating that work environment by parsial have an effect on signifikan of work satisfaction to PT. Perindustrian dan Perdagangan Bangkinang.Keywords: work environment, supervision dan work satisfaction.